Original researchVasopressor choice for hypotension in elective Cesarean section: ephedrine or phenylephrine? - Gunda, Chandrakala P.; Malinowski, Jennifer; Tegginmath, Aruna; Suryanarayana, Venkatesh G.; Chandra, Sathees B.C. (Archives of Medical Science, 2010)
Introduction: Hypotensive episodes are a common complication of spinal anesthesia during Cesarean section. The purpose of this study was to compare the effectiveness and the side effects of vasopressors, ephedrine and phenylephrine, administered for hypotension during elective Cesarean section under spinal anesthesia. Material and methods: The study consisted of 100 selected ASA I/II females scheduled for elective Cesarean section under spinal anesthesia. Each patient was randomly assigned to one of the two double-blind study groups. Group E received 1 ml ephedrine (5 mg/ml) with normal saline if hypotension was present (n = 50). Group P received 1 ml phenylephrine (100 µg/ml) with normal saline if hypotension developed (n = 50). Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP) were compared within and between groups to basal levels at time increments of 0, 2, 4, 6, 8, 10, 15, 20, 25, 30, 45, and 60 min from start of surgery. Incidence of side effects and neonatal outcomes were studied between groups. Results: All patients required vasopressor therapy for hypotension. Administration of phenylephrine was associated with significant drop in HR. Changes in SBP, DBP, and MAP were similar in both groups for most observed times. The incidences of nausea/vomiting and tachycardia were significantly higher in the ephedrine group. Conclusions : Phenylephrine and ephedrine are acceptable choices to combat maternal hypotension related to spinal anesthesia in elective Cesarean section. Complications of intra-operative nausea and vomiting, tachycardia and bradycardia should be considered when choosing a vasopressor, suggesting phenylephrine may be more appropriate when considering maternal well-being.